Pagans, Tartars, Moslems, and Jews in Chaucer's "Canterbury Tales" - Gretcheo Iman Meyer-Hoffman (American Journal of Islam and Society, 2002)
Brenda Deen Schildgen's analysis of the Canterbury Tales explores the contemporary worldviews of medieval Europeans. Chaucer, an English court poet, wrote probably his greatest work- the Canterbury Tales - at the end of the fourteenth century. It is a collection of 24 tales told by pilgrims as they make their way to Canterbury cathedral. Chaucer frames the tales with a prologue and dialogue between the tales. Schildgen's book examines the eight tales set outside Christian Europe. Much of the book discusses the medieval view of paganism and the continuing influence of pagan philosophy on medieval intellectual thought. She analyses the "Man of Law's Tale," whose story takes place in both pagan and Muslim lands. (It is worth pointing out here that, although by the fourteenth century the Mongols increasingly were becoming Muslims, the Tartars in the "Squire's Tale" are associated with paganism.) In addition to discussing the tales involving pagans and Muslims, Schildgen analyzes the anti-Semitic "Prioress' Tale." Drawing on Habermas's theory of practical discourse (in which discussants engage in a discourse where each is aware of and open to the other's perspectives and interpretations), Schildgen argues that the Canterbu,y Tales is an excellent example of what Habermas has in mind. Traditional analysis states that Chaucer does not favor one pilgrim over the others, and Schildgen takes this a step further by arguing that the Canterbury Tales incorporates "a range of intellectual and ethical attitudes that thrived in Chaucer's pan-European contemporary cultural and social world." She ...